Characterization of TRPV4-mediated signaling pathways in an optimized human choroid plexus epithelial cell line - Hulme, Louise; Hochstetler, Alexandra; Schwerk, Christian; Schroten, Horst; Ishikawa, Hiroshi; Tung, Chun-Yu; Perrin, Benjamin; Blazer-Yost, Bonnie (American journal of physiology. Cell physiology, 2022)
Download figureDownload PowerPoint